2010
DOI: 10.1080/10683161003752311
|View full text |Cite
|
Sign up to set email alerts
|

A study of psychotic disorders among female homicide offenders

Abstract: Although a considerable body of evidence has now accumulated about the link between psychotic illness and violent behaviour, fewer studies address this association in women. This data linkage study examined an entire population of female homicide offenders (N 055) in Victoria, Australia, over an eight-year period. Offence variables such as prior offending history and motivation for the offence were established by using police databases. The data were subsequently linked to a state-wide public mental health dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This may also go some way to explaining the gender differences found in the present study, specifically the low proportion of women recorded as being in their first episode and discrepancies arising with the meta‐analytic findings. Bennett and colleagues (35) reported that of the 55 women in the homicide cohort, 6 were murder‐suicide cases and only one of these had a previously recorded diagnosis on the public mental health database. This neatly highlights the perennial problem associated with the complexities of clinical presentation (30) and quality of record keeping and information sharing (10) between service providers and an inherent limitation with retrospective methodologies such as that employed here.…”
Section: Discussionmentioning
confidence: 99%
“…This may also go some way to explaining the gender differences found in the present study, specifically the low proportion of women recorded as being in their first episode and discrepancies arising with the meta‐analytic findings. Bennett and colleagues (35) reported that of the 55 women in the homicide cohort, 6 were murder‐suicide cases and only one of these had a previously recorded diagnosis on the public mental health database. This neatly highlights the perennial problem associated with the complexities of clinical presentation (30) and quality of record keeping and information sharing (10) between service providers and an inherent limitation with retrospective methodologies such as that employed here.…”
Section: Discussionmentioning
confidence: 99%
“…Women who kill are more often diagnosed with a severe mental disorder (18,34‐37) or a personality disorder, especially borderline (38‐40), in comparison with men who commit homicide (41,42). According to some studies (5,43), homicidal women are up to 43 times more likely to have a diagnosis of schizophrenia than the general population, although there is evidence that the diagnosis of schizophrenia may also be overestimated in homicidal women, and conversely, the psychopathic dimension may be underestimated (40,44,45). In our previous research, a significant correlation was found between the psychopathic dimension and borderline personality disorder in women who committed homicide (40).…”
mentioning
confidence: 99%
“…However, research has generally noted the shortage of research on SV offences committed by female offenders, due to low murder arrest rates (Chan & Frei, ) and small proportions of SV females. In comparison with previous research, this investigation has a relatively large sample size for a criminal female population; other research has utilised sample sizes that have varied from 16 to 55 to 204 female offenders (Bennett et al, ; Chan & Frei, ; Rossegger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive research of female offenders is limited as, for example, investigation of violent female offenders appears to include another aspect, such as a focus on IPV (e.g., Caman, Howner, Kristiansson, & Sturup, ; Thornton et al, ), sexual homicide (Chan & Frei, ), or psychotic disorders (e.g., Bennett, Ogloff, Mullen, & Thomas, ). In regard to the onset age of violence, research reports this to be earlier in female offenders (e.g., Moffitt, Caspi, Rutter, & Silva, ; Serbin & Karp, ); in comparison to non‐violent perpetrators, violent females were reported to be significantly younger (Goldstein & Higgins‐D'Alessandro, ; Pollock, Mullings, & Crouch, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation